SCIENCE AND TECHNOLOGY FOR THE REGION OF CAMBAI SUB-DISTRICT, PRABUMULIH ADMINISTRATIVE CITY - Mery Hasmeda (Lembaga Pengabdian pada Masyarakat, 2014)
Science and technology for the region of Cambai sub-district,Â Prabumulih Administrative city communities have been conducted from February to December 2010.Â The programs included training and demonstrationÂ as well as establishment of â€œDemplotâ€.Â The programs which have been conducted were training and demonstration of organic horticultural farming system, integrated organic farming, organic fertilizer, fish farming, chicken stock (ayam arab), and processing of fish feed and poultry feed. The programs were conducted integratedly with related institution of local goverment, university partner (Universitas Palembang) and Sriwijaya University.Â Several academic staff and students were also involved during implementation programs. The results showed that there were significantly increased in skills and knowledge of farmers especially in producing organic fertilizer, organic vegetables, integrated organic farming system, fish farmingÂ and chicken stock (ayam arab) inÂ better ways.Â Vegetable productions especially Kangkung, bayam, timun, terung were increased significantly compared to previous farming activitities which were not using organic fertilizer.Â In addition, farmers have capabilities to produce self fish feed and poultry feed without purchasing from the stores which were very expensive.Â Furthermore, the activity ofÂ target farmer groups were also improved in such a way which could make them more established in order to increase their income in agriculture production activities.